The Distribution of Rural Settlement Environmental Quality (Case at Bantul, DIY) - Ritohardoyo, Su (Universitas Muhammadiyah Surakarta, 1997)
The housing environment problem is the inreased population and housing densityÂ in certain areas, as a consequence of the high population growth rate. This situation has brought about the unavailability of the existing public facilities. Such as the evironmental problem is also faced by Bantul regency. Starting from those stated environment problems, this study has in phased its general objectives on to comprehend the variation of housing environmental quality within various topographical, and to comprehend environment factors influencing the housing environmental quality within various topographial background.this study employs so-called sampling technique. Area sampling is carried out aording to topographical condition. Ten villages are randomly selected representing the sampling areas. The number of respondent is 300 households, selected proportionally based on the area stratification. Primary data is collected direct communication with informants are key persons. Data analysis employed simple correlation technique, multiple regression analysis, and one way variance analysis. The study reveals that differences in topographical characteristics are strongly associated with the differences in the quality of housing environment. The level of village development is also the main variable determining the quality of housing environment. A significant different of housing environment quality both among various topographical zones and various level of village development is reported. The achievement of programs oriented to village environment improvement is varying according to the distribution of village on the topographical zone. A greater success is commonly achieved by villages located in the upland and low land than those in the hilly areas. The social-economic condition of the dwellers is determining the quality of housing environment. Nevertheless, differences in the contribution of various variables to housing environment are encountered. In the whole areas, whether it is lowland, hilly or uplands areas, the family inome to be the first important facctor determining the housing environment quality.